Calcium-amidoborane-ammine complexes: Thermal decomposition of model systems - Harder, Sjoerd; Spielmann, Jan; Tobey, Briac (Chemistry - A European Journal, 2012)
Hydrocarbon-soluble model systems for the calcium-amidoborane-ammine complex Ca(NH BH ) ·(NH ) were prepared and structurally characterized. The following complexes were obtained by the reaction of RNH BH (R=H, Me, iPr, DIPP; DIPP=2,6-diisopropylphenyl) with Ca(DIPP-nacnac)(NH )·(NH ) (DIPP-nacnac=DIPP-NC(Me)CHC(Me)N-DIPP): Ca(DIPP-nacnac)(NH BH )·(NH ) , Ca(DIPP-nacnac)(NH BH )·(NH ) , Ca(DIPP-nacnac)[NH(Me)BH ]· (NH ) , Ca(DIPP-nacnac)[NH(iPr)BH ]·(NH ) , and Ca(DIPP-nacnac)[NH(DIPP)BH ]·NH . The crystal structure of Ca(DIPP-nacnac)(NH BH )·(NH ) showed a NH BH unit that was fully embedded in a network of BH···HN interactions (range: 1.97(4)-2.39(4)Å) that were mainly found between NH ligands and BH groups. In addition, there were N-H···C interactions between NH ligands and the central carbon atom in the ligand. Solutions of these calcium-amidoborane- ammine complexes in benzene were heated stepwise to 60°C and thermally decomposed. The following main conclusions can be drawn: 1) Competing protonation of the DIPP-nacnac anion by NH was observed; 2) The NH ligands were bound loosely to the Ca ions and were partially eliminated upon heating. Crystal structures of [Ca(DIPP-nacnac) (NH BH )·(NH )] , Ca(DIPP-nacnac)(NH BH )·(NH ) ·(THF), and [Ca(DIPP-nacnac)NH(iPr)BH ] were obtained. 3) Independent of the nature of the substituent R in NH(R)BH , the formation of H was observed at around 50°C. 4) In all cases, the complex [Ca(DIPP-nacnac)(NH )] was formed as a major product of thermal decomposition, and its dimeric nature was confirmed by single-crystal analysis. We proposed that thermal decomposition of calcium-amidoborane-ammine complexes goes through an intermediate calcium-hydride-ammine complex which eliminates hydrogen and [Ca(DIPP-nacnac)(NH )] . It is likely that the formation of metal amides is also an important reaction pathway for the decomposition of metal-amidoborane-ammine complexes in the solid state. © 2012 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.